The Effect of Rose Aromatherapy on Anxiety Levels During the First Stage of Labor - Ira Titisari; Ni Putu Eka Nadya Saraswati Putri (Health and Technology Journal (HTechJ), 2025)
Maternal anxiety during labor is a common issue that can negatively affect the birthing process and maternal well-being. Rose aromatherapy effectively relaxes the muscles and mind, helping to loosen the uterine muscles and reduce the intensity of pain. This study aimed to determine the effect of rose aromatherapy on anxiety levels during the active phase of the first stage of labor. A quasi-experimental design with a non-equivalent control group was employed, involving 30 respondents who were divided equally into an intervention group and a control group. The research was conducted at Gurah and Sambi Community Health Centers from March to June 2023. Anxiety levels were measured using the DASS-21 scale, and data were analyzed using the Mann-Whitney test with a significance level of α = 0.05. The results showed that before the intervention, most respondents in the intervention group experienced moderate anxiety, while all respondents in the control group experienced severe anxiety. After administering rose aromatherapy, there was a significant reduction in anxiety levels among respondents in the intervention group compared to the control group (p-value = 0.000). These findings indicate that rose aromatherapy effectively reduces anxiety during the active phase of labor. It functions as a non-pharmacological method that stimulates the limbic system, promoting relaxation and a sense of comfort. The study concludes that rose aromatherapy can be recommended as a complementary intervention for mothers in labor to help manage anxiety. It also serves as a valuable reference for educational institutions, researchers, and healthcare professionals in developing evidence-based practices for maternal care.